1987
DOI: 10.1103/physrevlett.58.322
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear shapes from alphagamma-ray angular correlations

Abstract: The angular distribution of alpha particles with respect to the spin direction of the residual nuclei is used to probe the shapes of the emitting systems. Two compound systems have been studied: ' Yb and " Sn. Deformed emission shapes are required in order to understand the alpha-gamma correlations in the ' Yb system, but not for the " Sn compound system. These conclusions are identical to those reached by the study of giant resonances built on excited states for very similar systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…More than a decade ago, Gaardhoje et al [1] studied the shape of giant dipole resonance (GDR) built on excited states for ½¼ Sn and concluded that the data are consistent with a mostly spherical shape up to Ì ¾ ¼ MeV. A few years later Majka et al [2] reached a similar conclusion for ½½¼ Sn in a study of « -ray angular correlation measurements. Recently Bracco et al [10] have studied the dependence of the GDR width and angular distribution of the -rays as a function of temperature and spin for ½¼ ½½¼ Sn and concluded that due to thermal fluctuation effects the average deformation becomes very large at Ì ³ ¾ ¼ MeV and  ³ ¼ .…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…More than a decade ago, Gaardhoje et al [1] studied the shape of giant dipole resonance (GDR) built on excited states for ½¼ Sn and concluded that the data are consistent with a mostly spherical shape up to Ì ¾ ¼ MeV. A few years later Majka et al [2] reached a similar conclusion for ½½¼ Sn in a study of « -ray angular correlation measurements. Recently Bracco et al [10] have studied the dependence of the GDR width and angular distribution of the -rays as a function of temperature and spin for ½¼ ½½¼ Sn and concluded that due to thermal fluctuation effects the average deformation becomes very large at Ì ³ ¾ ¼ MeV and  ³ ¼ .…”
Section: Introductionmentioning
confidence: 87%
“…The partition function is given by  « Á ¿ ¾ Ì (2) where, corresponding to the laboratory Þ-axis cranking, the moment of inertia factor is given by…”
Section: Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…One example is the recent investigation of ~-~ angular correlations in compound nucleus reactions [1]. In this contribution we present the first results from an experiment designed to study the angular correlation of two successively emitted protons measured in coincidence.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of techniques have been employed in these studies. Some measurements have used the 7-ray hit pattern observed in a 4 rt spin spectrometer [1,2] to define an average spin orientation. Others have used fission fragments to determine the spin direction [3,4].…”
Section: Introductionmentioning
confidence: 99%